Broadband internet and the stock market investments of individual investors - Hans K. Hvide; Tom G. Meling; Magne Mogstad; Ola Lotherington Vestad (Statistics Norway, Research Department, 2021)
We study the effects of broadband internet use on the portfolio selection of individual investors. A public program in Norway provides plausibly exogenous variation in internet use. Our instrumental variables estimates show that internet use causes a substantial increase in stock market participation, driven primarily by increased fund ownership. Existing investors increase the fraction of their portfolios held in funds and do not increase their trading activity in stocks. Access to fast internet seems to induce individual investors to make better financial decisions and hence leads to a "democratization of finance".
Keywords: D83; G11; J2; 330; equity market participation; investor welfare; portfolio selection; stock market participation